The Impact of Information Technology Service Innovation and Service Quality on Customer Satisfaction in the Tourism Industry - Fonseca, Jesus Maia; Boquifai, Petronela (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The tourism industry has experienced significant transformation with the development of information technology (IT), which has had a major impact on the way services are delivered to customers. Technological innovations, such as online booking platforms, mobile applications, and the use of artificial intelligence (AI), have increased the efficiency and ease of access to tourism services. In addition, high service quality, which includes speed, responsiveness, and ease of interaction, is an important factor in increasing customer satisfaction. High customer satisfaction can increase loyalty, increase the likelihood of customers returning to use the same service, and provide positive recommendations. Therefore, understanding the relationship between IT service innovation, service quality, and customer satisfaction is essential for companies in the tourism sector to maintain competitiveness in an increasingly competitive market. This study aims to examine the impact of IT service innovation and service quality on customer satisfaction in the tourism industry, as well as providing insight for companies in facing challenges and taking advantage of existing opportunities.